Ceos' cognitive maps and the scope of the organization - Calori, Roland; Johnson, Gerry; Sarnin, Philippe (Strategic Management Journal, 1994)
In this paper, CEOs are considered as ‘cognizers’ charged with integrating views in the top management team; a role which should require high cognitive complexity especially in diversified multinational corporations. A methodology for studying top managers' cognitive complexity is described and then applied to a sample of 26 CEOs. The CEOs' cognitive maps of the structure and of the dynamics of their industry are analyzed in terms of their degree of complexity, in relation to the breadth of the business portfolio of the firm, its geographic scope and the links the firm has with foreign parents. The results of this exploratory test generally confirm the principle of requisite cognitive complexity, and reveal a new set of more precise hypotheses linking particular dimensions of the scope of the firm with particular dimensions of CEOs' cognitive complexity.